2023
DOI: 10.3390/ijerph20031792
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Channel Pricing Decisions for Product Recycling in Green Supply Chain Operations: Considering the Impact of Consumer Loss Aversion

Abstract: With the vigorous rise of online third-party recycling platforms, dual-channel recycling has become the primary recycling mode in the reverse supply chain (RSC). However, as the main body of recycling, consumers have a significant impact on the recycling process, and their behavioral preferences are rarely considered in the pricing decision of the reverse recycling supply chain. Based on the dual-channel RSC, this paper considers the competition among channels. It introduces the loss aversion behavior preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…This section establishes a model of a supply chain system with dual channels [21] and supply failures [5]. We completed the work in four steps.…”
Section: Problem Definition and Formulationmentioning
confidence: 99%
“…This section establishes a model of a supply chain system with dual channels [21] and supply failures [5]. We completed the work in four steps.…”
Section: Problem Definition and Formulationmentioning
confidence: 99%
“…For example, Pal and Sarkar [31] proved that channel price sensitivity could affect the profit of dual-channel supply chain members. Based on the reverse supply chain perspective, Xu et al [32] analyzed the impact of consumer loss aversion behavior on the recycling pricing and profit of each node in the supply chain. Abhijit et al [33] showed that government subsidies are beneficial for the suppliers and manufacturers of a three-layer green supply chain model with a dual-channel structure, and they can reduce the cost of green products.…”
Section: Literature Reviewmentioning
confidence: 99%